2016
DOI: 10.1109/tcc.2015.2453988
|View full text |Cite
|
Sign up to set email alerts
|

On Achieving Energy Efficiency and Reducing CO2Footprint in Cloud Computing

Abstract: With the increasing popularity of the cloud computing model and rapid proliferation of cloud infrastructures there are increasing concerns about energy consumption and consequent impact of cloud computing as a contributor to global CO2 emissions. To date, little is known about how to incorporate energy consumption and CO2 concerns into cloud application development and deployment decision models. In this respect, this paper describes an eco-aware approach that relies on the definition, monitoring and utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…On account of the distributed storage benefit must be adaptable, security limits and assurance hardware can't be unmistakably characterized, which builds some trouble for the usage of particular assurance measures; [8](2) the distributed storage transmits information through the system. The benefit interferences, information devastation, data stolen furthermore, altered caused by the noxious assaults in the organize represent a serious test to the security of information correspondences, get to confirmation and classification; [9](3) from the client's view, the distributed storage of information makes distributed computing specialist co-op gets the information get to control, and the client's information is looked with protection security dangers. Individuals stress over that the touchy individual information will be exposure, abuse or missing by putting the information in cloud condition [10].…”
Section: Overview: Security Issues In Cloud Computingmentioning
confidence: 99%
“…On account of the distributed storage benefit must be adaptable, security limits and assurance hardware can't be unmistakably characterized, which builds some trouble for the usage of particular assurance measures; [8](2) the distributed storage transmits information through the system. The benefit interferences, information devastation, data stolen furthermore, altered caused by the noxious assaults in the organize represent a serious test to the security of information correspondences, get to confirmation and classification; [9](3) from the client's view, the distributed storage of information makes distributed computing specialist co-op gets the information get to control, and the client's information is looked with protection security dangers. Individuals stress over that the touchy individual information will be exposure, abuse or missing by putting the information in cloud condition [10].…”
Section: Overview: Security Issues In Cloud Computingmentioning
confidence: 99%
“…(Kurpicz et al, 2016). The CO 2 emissions depends on the energy consumption and on the electricity mix (Wajid et al, 2015). One could compute these costs at each time and divide them proportionally to the number of resources booked by each VM.…”
Section: From the Cloud User Point Of Viewmentioning
confidence: 99%
“…While the live monitoring issue has already been addressed in literature (Wajid et al, 2015), the accounting issue has received little attention.…”
Section: Introductionmentioning
confidence: 99%
“…While these metrics are useful for assessing energy efficiency, they are difficult to apply in case the need of evaluating the energy consumption of an application arises, since they provide only a relative evaluation (i.e., percentage) of the consumption. To be able to assess if reserved resources for an application are being used effectively, in the ECO 2 Clouds project [3,17], new metrics have been introduced to evaluate energy efficiency not only at the infrastructure and data center levels, but also at the application level [18]. The proposed metrics are relative metrics that allow assessing the percentage of waste at the application level, but do not focus on directly measuring power or energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…Other cases considered in the study showed characteristics similar to one of the aforementioned two cases. An experimental analysis of the possible different configurations was studied through simulation and comparing the results in a federated cloud environment, provided within the ECO 2 Clouds project [17]. Within ECO 2 Clouds, the main focus was on deploying VMs so that CO 2 emission is minimized, through adaptive scheduling algorithms based on the monitored ecometrics.…”
Section: Related Workmentioning
confidence: 99%